Effect of operational parameters on fouling in membrane bioreactor - Tan, Mong Ai. (2008)
Prior to the pilot study, this dissertation will consolidate the factors that can strongly influence membrane fouling. It was found that it is desirable to operate at high MLSS levels and long SRT as sludge yield will be reduced and a smaller reactor is sufficient.